System of Payroll in the Public Sector Administration - Jibrin, Musa Success; Ejura, Success Blessing; Augustine, Nwaorgu Innocent (Asian Development Policy Review, 2015)
Salary payments in the public sector administration are a key to service success, performance effectiveness and efficiency. Be that as it may, this write up was painstakingly tailored to lay much emphasis on the importance of labour and wages in the public sector management. Pay roll system in the public sector administration lays emphasis on productivity and prompts remunerations. In going about these various payroll preparation methods purported efforts were made to demonstrate how far adoptable the system are in bringing about effective and efficient salaries and wages administration in the public sector. Various outstanding remuneration literatures were reviewed and far reaching observations were advanced to do justice to the subject matter. However, a lot still beckons salaries wages scholars to lend their voices for the larger benefit of man.